Shock front loading techniques for studies in dynamic photoelasticity - Miles, Anthony William (Department of Mechanical Engineering, 2016)
A technique has been developed, whereby the shock front produced in a shock tube can be used to apply a well-defined dynamic load for studies in dynamic photoelasticity. A brief review is given of the techniques that have been used, and the scope of research projects that have been undertaken in dynamic photoelasticity by other investigators. The theory related to shock front loading of models is presented. The work that has been carried out for this research project includes: The modification of an existing shock tube facility to accommodate a test section with parallel optical windows. The evaluation of the shock tube performance and the measurement of loading cycles imparted to models subjected to shock front impact. The design of a model housing to enable mounting a photoelastic model in the test section. The development of an optical system to enable photographing the dynamic fringe patterns produced in photoelastic models subject to shock front impact. A selection of photographs showing the dynamic fringe patterns produced in the models is included in this thesis and the dynamic stresses resulting from the loading method discussed. The results show that the technique could be extremely useful for studying dynamic stresses in models and some suggestions for future applications of the technique are given.